Implementasi Program Kemitraan Dan Bina Lingkungan (PKBL) dan Kendala (Studi pada PT Waskita Karya (Persero) Tbk - Faza Ihya Sya’bana; Sri Bakti Yunari (Jurnal Pengabdian Masyarakat Madani, 2021)
The implementation of the Partnership Program is a program to increase the ability of small businesses to become resilient and independent and Community Development is a program for empowering the social conditions of the community, hereinafter referred to as PKBL by State-Owned Enterprises (BUMN) in the vicinity of the SOE's operations. As one of the leading SOEs, PT. Waskita Karya Tbk. also implement, but in its implementation there are still discrepancies and obstacles. The problem in this scientific paper is how the PKBL implementation of PT Waskita Karya (Persero) Tbk is compatible with SOE PERMENEG Number PER-09/MBU/07/2015 and what obstacles are faced by PT Waskita Karya (Persero) Tbk. in the implementation of the PKBL. The research method used is a descriptive normative juridical research using secondary data which is analyzed qualitatively by means of deductive logic. Based on the research results of PT Waskita (Persero) Tbk, there is still a discrepancy with the PERMENEG BUMN Number Per-09/Mbu/07/2015. The constraints faced in the implementation of PKBL by PT Waskita Karya (Persero) Tbk are due to limited human resources and also accessibility to conduct field surveys. There are also some fostered partners who do not have good faith in the implementation of the Partnership Program.